Improvement of antibody functionality by structure-guided paratope engraftment - Qingbo Liu (Nature Portfolio, 2019)
Quaternary contacts mediated by an extended heavy-chain framework region 3 (FR3) have been shown to improve binding to HIV envelope and virus neutralization for a few antibodies. Here, Liu et al. engraft such an FR3 loop onto several potent broadly neutralizing antibodies, resulting in improved neutralization activity and pharmacokinetics.